Farmer preferred traits and genotype choices in Solanum aethiopicum L., Shum group - Nakyewa, Brenda; Sseremba, Godfrey; Kabod, Nahamya Pamela; Rwothtimutung, Moses; Kyebalyenda, Tadeo; Waholi, Kenneth; Buteme, Ruth; Nakanwangi, Mildred Julian; Bishop, Gerard; Balyejusa Kizito, Elizabeth (Journal of ethnobiology and ethnomedicine, 2021)
Solanum aethiopicum L. is a nutrient dense African indigenous vegetable. However, advancement of its improved varieties that can increase productivity, household income, and food security has not been prioritized. Further still, studies on some of the crops that have been worked have indicated that it is not a guarantee that the improved varieties will be accepted by the end users and therefore there is need to identify and profile what genotypes are of interest to farmers and their preferred traits through inclusive participatory evaluations. Methodology: Farmer participatory evaluations were conducted to profile farmers’ traits of interest and preferred genotypes. A total of 24 genotypes were established in three replications in 6 farms in 3 districts; Wakiso, Mukono, and Luwero as these are the major producing districts of the vegetable in Uganda. A total of 177 sex-disaggregated farmers were engaged in scoring the genotypes for pest, disease and drought tolerance, general appeal, leaf yield, leaf texture, and seed yield for best 10 genotypes under each variable. Results: Non-significant differences in trait (p > 0.05) and genotype preferences (p > 0.05) were obtained between men and women. The most desired farmer traits were seed and leaf yield, followed by pest and disease resistance. The overall preferred genotype in terms of disease and pest resistance, leaf yield, leaf texture, and seed yield were E12 followed by E11. Conclusion: Gender does not seem to influence farmer choices for the S. aethiopicum, Shum group, indicating an opportunity for single variety prototype advancement by breeders and dissemination by seed companies.
Keywords: African indigenous vegetables; Farmer trait preferences; Variety adoption